A Study on Mechanical Properties of Conventional Concrete and Coconut Shell Concrete by Replacing Cement with Silica Fume - R.Prasath Kumar, V; Gunasekaran, K; K P, Sreerag (International Journal of Engineering and Technology, 2018)
High standing estimation of building materials utilized for development is a component of incredible concern. Coconut shell as a completely substitution in the place of coarse aggregate may totally effective for designers in construction industry. The coconut shell concrete is a light weight solid which may decrease the self-heap of a structure. The under taken project depends on inspecting attributes of coconut shell concrete when contrasted with conventional concrete. Coconut shells going from 10mm strainer and held on 6.3mm were considered to utilize for this study. For the current study M100 grade concrete is used to cast the specimens. The principle properties considered testing on coconut shell concrete and conventional concrete is compressive strength, split tensile strength and flexural strength. Examples were taken by supplanting coarse aggregate with coconut shells completely and cement is supplanted by silica fume with various extents of 5%, 10%, 15%, 20%, 25% for compressive strength test and tests were done at 3, 7, 28, 56 and 90 days of curing, it is observed that the ideal compressive strength outcomes were obtained at 10% of silica fume. The flexural strength and  split tensile strength of the specimens are calculated with replacement of cement by silica fume with  different extents of 0%, 5%, 10% and 15%, tests were done at 3, 7 and 28 days of curing. The optimum replacement percentage of cement by silica fume is 10% for compressive strength, split tensile and flexural strength. The primary principle is to lessen the utilization of natural aggregate by supplanting them with coconut shells and to decrease the density of concrete which makes concrete for simple dealing.